Pollutant footprint analysis for wastewater management in textile dye houses processing different fabrics - Sözen, Seval; Dulkadiroglu, Hakan; Begum Yucel, Ayse; Insel, Guclu; Orhon, Derin (Wiley, 2019)
AbstractBACKGROUNDThis study investigated the water and pollution footprints of a dye house, which processed cotton knits, polyester (PES) knits and PES‐viscose woven fabrics. Experimental evaluation was carried out for each processing sequence. Variations in wastewater flow and quality were established as a function of the production program in the plant. A model evaluation of wastewater dynamics was performed and defined specifications of an appropriate treatment scheme.RESULTSThe plant was operated with a capacity of 4300 t year−1 of fabric, which generated a wastewater flow of 403 500 m3 year−1 and a COD load of 675 t year−1. The overall wastewater footprint of the plant was computed as 91 m3 t−1 and the COD footprint as 160 kg t−1 of fabric. Depending on the fabric type, results indicated expected changes in wastewater flow between 600 and 1750 m3 day−1; in COD load between 1470 and 2260 kg day−1 and in COD concentration between 1290 and 3400 mg L−1.CONCLUSIONA model simulation structured upon COD fractionation and related process kinetics revealed partial removal of slowly biodegradable COD, coupled with high residual COD, which would by‐pass treatment. Resulting biodegradation characteristics necessitated an extended aeration system, which could also enable partial breakdown of residual COD. Effluent COD could be reduced to 220–320 mg L−1 with this wastewater management strategy. © 2018 Society of Chemical Industry
Keywords: Wastewater footprint; Modeling; Treatment optimization; COD footprint; Textile dyeing